An Important Study of the Ethics of Pilgrimage - Jurayeva Nafisa Olimovna (Zien Journals, 2022)
This article analyzes the data on the historical topography of the tombs of Bukhara, cited in the work of Ahmad ibn Mahmud “History of Mullozoda”. It is also argued that the work is useful for clarifying the pilgrimage issues that are important to the pilgrim, the possibility of visiting the cemetery by men and women, the etiquette of visiting the grave, the recommendations on the etiquette of pilgrimage still serve as a guide for today.
Keywords: culture of pilgrimage; pilgrimage etiquette; holy shrine; pilgrimage issues